Reliability of muscular activation patterns and their alterations during incremental handcycling in able-bodied participants - Quittmann, O. J.; Abel, T.; Albracht, K.; Strüder, H. K. (Sports Biomechanics, 2021)
The aim of this study was to assess muscle activity patterns (MAPs) in handcycling in terms of reliability and their alterations due to increasing workload. A total of 12 able-bodied triathletes performed an incremental step test until subjective exhaustion in a racing handcycle that was mounted on an ergometer. During the test, muscular activity of 10 muscles of the upper extremity and trunk was measured using surface electromyography (sEMG). MAPs were examined by calculating integrated EMG (iEMG), the onset, offset and range of activation (RoA). Parameters of MAPs were analysed using intraclass correlation coefficient (ICC) and two-way ANOVA with repeated measures. ICCs ranged from 0.775 to 0.999 indicating `good` to `excellent` reliability. All muscles increased their iEMG from low to high intensity with differing effect-sizes. Several muscles showed an earlier onset and increased RoA. MAPs in handcycling are highly reliable and alterated due to increasing workload in able-bodied participants. Whereas muscular effort can be examined in a single cycle, muscle activation characteristics require at least six to ten consecutive revolutions to achieve `good` or `excellent` reliability. At high intensity, many muscles demonstrated an earlier onset and larger RoA. Future studies should validate these findings in several elite handcyclists and investigate all-out sprint exercises.